Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3746/pnf.2012.17.1.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-treatment and Storage Conditions on the Quality Characteristics of Ginger Paste

Abstract: This study was performed to investigate the effects of pre-treatment and storage temperature and periods on the quality characteristics of ginger paste. The pH of the ginger paste remained constant during room temperature storage but increased with prolonged refrigerated storage periods. During five months of frozen storage, regardless of pre-treatment, the pH of most of the samples decreased slightly and then remained constant. In the color value of ginger paste stored at room temperature, the samples with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Non significant difference (p<0.05) was observed in titrable acidity of dried powder. Similar results were also observed by Choi et al (2012). The mineral contents and phytochemicals of produced ginger powder are presented in Table II.…”
Section: Resultssupporting
confidence: 86%
“…Non significant difference (p<0.05) was observed in titrable acidity of dried powder. Similar results were also observed by Choi et al (2012). The mineral contents and phytochemicals of produced ginger powder are presented in Table II.…”
Section: Resultssupporting
confidence: 86%
“…After 8 months of storage, the loss of 6-gingerol content was 59.1 and 79.5 %, in Halia bentong and 19.0 and 79.3 % in Halia bara, at 5 °C and 15 °C, respectively, whereas that of 6-shogaol content was 47.0 and 82.9 % in Halia bentong and 25.1 and 56.7 % in Halia bara, at 5 °C, and 15 °C respectively. A recent study, reported a decrease of total gingerol content (83.3 %) in ginger rhizomes during storage at freezing temperature [ 20 ].…”
Section: Resultsmentioning
confidence: 99%